Review: Sentimentality Reloaded. Reconsiderations of Romantic Sentimentality in Nineteenth-century Bolivia Today. (Periphērica: Revista de Historia Social, Cultural, y Literaria, 2019)
Book Review of Leonardo García Pabón. El cuento sentimental romántico en Bolivia (siglo XIX). La Paz: Plural Editores, 2017. 457 pp.